The role of university and image of entrepreneurship on entrepreneurship inclination of engineering students - Ngah, Rohana; Buyong, Siti Zahrah; Sarmidy, Rahimah; Abdul Rahman, Rafidah (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2012)
This study investigates the inclination towards entrepreneurship amongst engineering students. The main aims are to examine the relationship between the role of university, image of entrepreneurship and inclination towards entrepreneurship. An empirical test of pilot study was carried out on the data gathered from seventy-one questionnaires demonstrates that university role and image of entrepreneurship have significant relationship on entrepreneurship inclination among students. Male students have higher inclination of entrepreneurship than female students. However, past working experience and participation in entrepreneurship program in university have small impact on students’ inclination towards entrepreneurship. Finally, based on the findings of the pilot study, implications of the study have been forwarded.